The Effect of Gamification on Primary Students' Malay Reading Comprehension - Felicia, Nasip; Norehan, Zulkiply (Secholian Publication, 2024)
Reading is a fundamental ability crucial for everyday life, including learning. Research on reading comprehension has intrigued scholars, resulting in various studies to uncover effective strategies for enhancing students' reading comprehension. In the Bahasa Melayucurriculum of Malaysian education, fostering students' reading and comprehension skills is crucial. This study aims to examine whether students' Malay reading comprehension could be enhanced using gamification methods. This study employed an experimental design, and a total of 74students, aged between 10 and 11 years and encompassing both males and females, participated in the study. The participants were from primary schools located in a rural district. An independent-sample t-test analysis revealed a significant difference in Malay reading comprehension among participants exposed to different instructional methods. Specifically, participants who engaged with the gamification method outperformed their counterparts who adhered to the traditional method. These findings offer valuable insights for educators aiming to incorporate gamification into reading comprehension instruction. The implications of this study's findings extend to educational practitioners, providing guidance on the integration of gamification into the reading comprehension curriculum. Furthermore, these results hold the potential to inform the Ministry of Education in Malaysia, supporting the advancement of gamification-based learning initiatives